Jawaharlal Nehru on Community Development - Planning Commission (Planning Commission, 1957)
The reflections of Jawaharlal Nehru on Community Development, articulated during project inaugurations between 1952 and 1957, present a visionary framework for nation-building rooted in participatory democracy and human-centered progress. Conceiving development as a collective enterprise in which every citizen is a stakeholder in “India Limited,” Nehru emphasized that the true objective of the Community Development Programme was not merely the creation of physical infrastructure but the transformation of individuals into conscious, confident contributors to national advancement. He underscored the importance of dynamic leadership that inspires rather than dictates, advocating grassroots engagement, decentralized initiative, and close interaction between officials and villagers to ensure organic and sustainable growth. Education, capacity building, and the dignity of labor were central to his philosophy, with an insistence that development workers remain closely connected to the communities they serve. Nehru highlighted inclusivity and equality of opportunity, particularly for marginalized and economically backward groups, aligning community development with the broader goal of establishing a socialistic pattern of society grounded in democratic values. While acknowledging challenges such as the gap between planning and implementation, he called for flexibility, realistic resource assessment, and continuous adaptation to local cultural contexts. Ultimately, Nehru envisioned Community Development as a transformative movement capable of fostering self-reliance, social cohesion, and holistic rural transformation, thereby shaping a progressive and participatory democratic India.
The Publications Division
The Publications Division
Keywords: Community Development Programme; Participatory Governance; Five Year Plan; Democratic Decentralization; Rural Transformation; Grassroots Leadership; Social Equality; Capacity Building; National Development; Inclusive Growth; Human-Centered Development; Socialistic Pattern Of Society